2014
DOI: 10.1186/0717-6287-47-12
|View full text |Cite
|
Sign up to set email alerts
|

Compositional studies and Biological activities of Perovskia abrotanoides Kar. oils

Abstract: Background Current study has been designed to evaluate the chemical composition of essential and fixed oils from stem and leaves of Perovskia abrotanoides and antioxidant and antimicrobial activities of these oils. Results GC-MS analysis of essential oil identified 19 compounds with (E)-9-dodecenal being the major component in stem and hexadecanoic acid in leaves. In contrast, GC-MS analysis of fixed oil showed 40 constituents with α-amyrin th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 21 publications
2
10
1
Order By: Relevance
“…The obtained results were similar to the previously published data for the plant from Iran, where 1,8‐cineole, δ ‐3‐carene, camphor, myrcene, and β ‐caryophyllene were identified as the major EOs compounds . Comparing the results obtained in this study with the other reported for samples collected in Pakistan, a noticeable variation in composition and percentages of components can be observed. The major components of P .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The obtained results were similar to the previously published data for the plant from Iran, where 1,8‐cineole, δ ‐3‐carene, camphor, myrcene, and β ‐caryophyllene were identified as the major EOs compounds . Comparing the results obtained in this study with the other reported for samples collected in Pakistan, a noticeable variation in composition and percentages of components can be observed. The major components of P .…”
Section: Resultssupporting
confidence: 91%
“…The obtained results were similar to the previously published data for the plant from Iran, where 1,8-cineole, d-3-carene, camphor, myrcene, and b-caryophyllene were identified as the major EOs compounds. [27 -30] Comparing the results obtained in this study with the other reported for samples collected in Pakistan, [71] a noticeable variation in composition and percentages of components can be observed. The major components of P. abrotanoides essential oil from Pakistan (stem and leaves) were (E)-9-dodecenal (66.5%), hexadecanoic acid methyl ester (27.79%), lupeol (21.5%), octadecenoic acid methyl ester (18.45%), eicosane (6.22%), tetradecane (5.19%), octadecanoic acid methyl ester (8.37%), and 2,2,5, 5-tetramethylhexane (3.96%).…”
Section: Chemical Diversity Of the Essential Oilssupporting
confidence: 56%
“…Radical scavenging activity values also revealed similar trend (Figure 3b). The results reported by Ashraf et al [38] on the DPPH contents of P. abrotanoides leaves and stems were not comparable with ours, probably due to differences in standards and experimental conditions. [39] However, our results are confirmed by those obtained for seven Salvia species by Aghaei Jeshvaghani et al [36] who reported IC 50 values in the range of 198 lg/ml in S. virgata to 1810 lg/ml in S. persica.…”
Section: Antioxidant Capacitycontrasting
confidence: 99%
“…[40] As shown in Figure 4, the strongest activity (i.e., the lowest EC 50 ) was recorded for PMASA with an EC 50 value of 0.039 mg/ml while PKRGS recorded the lowest. Ashraf et al [38] also reported the highest reducing power in Perovskia leaves. Experimenting with Salvia species, Aghaei Jeshvaghani et al [36] reported reducing powers similar to the ranges observed in the present study.…”
Section: Antioxidant Capacitymentioning
confidence: 91%
“…Cut [S] A sharp cut is made on the ear of the animals. T [72], Seriphidium brevifolium [73] etc. However further details about the phytochemicals from several other plant species are given in Table 9.…”
Section: Retention Of Placentamentioning
confidence: 99%